ANALISIS PERAN PENDIDIKAN KEWIRAUSAHAAN, KEPRIBADIAN, DAN LINGKUNGAN TERHADAP MINAT SISWA SMK UNTUK BERWIRAUSAHA DI KOTA BEKASI - Lutfiadi, Ridwan; Rahmanto, Muhammad Ikhwan (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2011)
Entrepreneurship education has so far been considered as one of the important factors to grow and develop the passion, spirit, and entrepreneurial behavior among the younger generation, but an attempt to examine its effectiveness would have been indispensable. For that, need to be investigated are the dominant variables that affect the interest of the students for entrepreneurship. In this case in addition to entrepreneurial learning, have also investigated the extent to which the role of personality and interest in the entrepreneurial environment of vocational students.The purpose of this study is to investigate and analyze the role of entrepreneurial learning, personality, interest in entrepreneurship and the environment against vocational students in the city of Jakarta. The results show that education does not play a role in fostering interest in entrepreneurship, while the personality and the environment play a role in fostering students' interest in entrepreneurship in vocational Bekasi.